PEMENUHAN HAK KONSUMEN ATAS UANG SISA TRANSAKSI BAHAN BAKAR MINYAK OLEH PELAKU USAHASTASIUN PENGISIAN BAHAN BAKAR UMUM DI KECAMATAN MARPOYAN DAMAI KOTA PEKANBARU - Dicky Ramandha Putra; Maryati Bachtiar; Dasrol Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Article 7A UUPK stipulates that business actors are obliged to have good faith in conducting theirbusiness activities, including in fulfilling consumer rights to the remaining money on fuel oil transactions atgas stations. In Pekanbaru City there are 47 Pertamina gas stations that operating every day and for theMarpoyan Damai sub-district there are 5 gas stations and there are 3 gas stations that the authors chooseto be research locations, but in reality the gas stations do not fulfill consumer rights for the remainingpayment transactions, so that the remaining money consumer payment transactions that are not fullyreturned are detrimental to the consumer. The purpose of writing this research, namely; First, to find outconsumers feel disadvantaged by the price rounding action on the remaining money from fuel oiltransactions by the public refueling station business. The second is to knowing the mechanism for fulfillingconsumer rights to the remaining fuel oil transactions by business actors Public refueling stations. The thirdis to knowing the efforts to fulfill consumer rights to the remaining money for fuel oil transactions by publicrefueling station operatorsThe type of this research can be classified in sociological research. This research uses libraryresearch and field research to obtain data. This research was conducted at Pertamina Gas Station inPekanbaru City. While the population and samples are the overall parties related to the problems examinedin this study. The data sources used primary data and secondary data, data collection techniques in thisstudy by observation, interviews, questionnaires and literature studies.Based on the results of the problem research, there are three points that can be concluded. Firstconsumers feel disadvantaged by rounding out the remaining money in the fuel transaction at the gasstation. Secondly, the mechanism for fulfilling consumer rights for the remaining money from oil fueltransactions is regulated legally by gas stations. Third, efforts that can be made to overcome the obstaclesto the fulfillment of consumer rights for the remaining money from fuel oil transactions at gas stations,namely by increasing the knowledge of consumers and business actors on their rights and obligations.Author's suggestion are first, consumers must be smarter in conducting buying and selling transactions andbroadening their knowledge horizons as consumers and business actors must carry out their business inaccordance with the provisions regulated by law. Secondly, for the Gas Station owners is to make a legalrule regarding the mechanism of fuel oil transaction transactions. The third is more active in disseminatingconsumer protection, especially in the rights and obligations of consumers and business actors.Keywords: Protection - Consumers - Transactions - Gas stations